A Study on Creation of Brand Image through Social Media - Kanojia, Babita A. (SFIMAR Research Review, 2017)
Earlier the brand image of the organization was created with the help of word of mouth. Just as the customer is the monarch of the market, same way now social mass media has become the monarch in terms of brand formation for any and every organization beginning from a start-up to an established organization. The concept of Creating Brand Image via Social Media is at the top of the schedule for many business officials today. Pronouncement makers as well as mentors, try to recognize ways in which firms can make gaintul use of solicitations such as Wikipedia, YouTube, Facebook, Second Life, and Twitter. Yet despite this interest, there seems to be very limited understanding of what the term "Brand Image" exactly means. This paper intends to provide some explanations for the same. We begin by unfolding the concept of Brand Image. Based on this definition, we then provide a classification of Social Media which groups applications currently included under the generalized term into more specific categories by characteristic: blogs, social networking sites, and virtual social worlds.